A new approach to infer changes in the synchronization of business cycle phases - Danilo Leiva-Leon (Bank of Canada, 2014)
This paper proposes a Markov-switching framework to endogenously identify the following: (1) regimes where economies synchronously enter recessionary and expansionary phases; and (2) regimes where economies are unsynchronized, essentially following independent business cycles. The reliability of the framework to track changes in synchronization is corroborated with Monte Carlo experiments. An application to the case of U.S. states reports substantial changes over time in the cyclical affiliation patterns of states. Moreover, a network analysis discloses a change in the propagation pattern of aggregate contractionary shocks across states, suggesting that regional economies in the United States have become more interdependent since the early 1990s.
Keywords: E32; C32; C45; 330; Business fluctuations and cycles; Econometric and statistical methods; Regional economic developments